Apartheid - Bruhns, Una D. (Canada: Friesen Press, 2023)
"On Challenging Journeys We Find Out Who We Are. Apartheid is a powerful memoir of Una's personal and political struggles growing up in the peaceful community of Vrededorp, Johannesburg, South Africa. By age nine, the political arena in South Africa changed; Una and her family are assessed, segregated and uprooted from their home in Vrededorp by the Aparteid Authorities and moved to Coronationville, a Johannesburg suburb. Witnessing "The Sharpville Massacre" in March 1960, a sudden shift of lens brought a new focus on her young mind that forever changed how she viewed those in power. After a failed marriage, she is now a single mother and determined to find a better life for herself and her son. She falls in love with a German immigrant. With her fierce spirit, she begins challenging the Immorality law and they fight for their love under the watchful eye and harassment of the local police. Her poems bring raw vulnerability and frustration to the forefront of what it feels like to be held back and watch injustice continue." -- Back cover.
Keywords: Bruhns, Una D; Apartheid -- South Africa -- Biography; Apartheid -- Afrique du Sud -- Biographies; Apartheid; Johannesburg (South Africa) -- Biography; South Africa -- Biography; South Africa; South Africa -- Johannesburg; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Autobiographies